Urban Food Security: Instalasi Bottle Aquaponics untuk Mewujudkan Ketahanan Pangan Berkelanjutan - Anang Kistyanto; Febrika Yogie Hermanto; Amirusholihin Amirusholihin; Muhammad Fajar Wahyudi Rahman; Restu Eri Adinata (SEMANGGI : Jurnal Pengabdian kepada Masyarakat, 2026)
Urban food security in rapidly urbanizing contexts remains constrained by limited land availability and weak community-level adoption of sustainable food practices. Although urban farming is widely promoted, existing approaches are predominantly technocentric and insufficiently integrate experiential learning, community empowerment, and scalable dissemination mechanisms. This study is among the first to propose and empirically demonstrate an integrative model that combines low-cost bottle aquaponics, experiential learning, and educational tourism (eduwisata) as a community-based diffusion platform. Using an Asset-Based Community Development (ABCD) approach, the intervention was implemented through field assessment, participatory training, and experiential dissemination. The findings reveal that simple, highly replicable systems significantly enhance food literacy, technical capability, and adoption intention, while eduwisata accelerates diffusion beyond initial participants. This study advances urban food security literature by bridging technological and social dimensions and offers a scalable pathway linking education, local food production, and community empowerment in resource-constrained urban environments.